Blood selenium level and glutathione peroxidase activity as affected by high level of selenium supplementation in cattle and buffaloes: A comparative study - DATT, CHANDER; CHHABRA, ARUNA (The Indian Journal of Animal Sciences, 2014)
An experiment was conducted in order to study the effect of level of dietary selenium (Se) on blood Se concentration and erythrocyte glutathione peroxidase (GSH-Px;EC 1.11.1.9) activity in cattle and buffaloes. For this, 10 male calves of crossbred cattle (Karan Fries) were randomly distributed into 2 groups of 5 animals each. Likewise, 10 male calves of Murrah buffaloes were divided into 2 groups. Within species, the average weight of2 groups were similar. The animals in group 1 (low-Se) were fed on basal ration consisting of paddy straw and concentrate mixture to meet their requirements, The animals in group 2 (high -Se) were supplemented with 2,7 ppm of Se as sodium selenite over and above the basal ration. The animals in both the groups were also supplied with green maize fodder so as to meet their vitamin A needs. Dietary N:S ratio Was in the optimum range. Blood Se concentration as well as GSH-Px activity during 60 days of experimental feeding were significantly (P